2021
DOI: 10.1097/brs.0000000000004043
|View full text |Cite
|
Sign up to set email alerts
|

Wide Laminectomy, Segmental Bilateral Laminotomies, or Unilateral Hemi-Laminectomy for Lumbar Spinal Stenosis

Abstract: Study Design. Propensity-matched retrospective study of patients prospectively enrolled in Danespine.Objective. The aim of this study was to report 5-year patient reported outcome in lumbar spinal stenosis (LSS) patients who underwent wide laminectomy (WL), segmental bilateral laminotomies (SBL), or unilateral hemilaminectomy (UHL) with bilateral decompression. Summary of Background Data. The optimal procedure for LSS remains controversial. Studies have shown no difference in short term outcomes among micro-la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…The study found that 91% of patients reported being satisfied with their surgery, and 92% reported an improvement in their symptoms. In a more recent study by Bouknaitir et al, 2021, patient satisfaction was evaluated after lumbar decompression surgery using a validated questionnaire [16]. The study found that 87% of patients reported being satisfied with their surgery, and 85% would choose to have the same surgery again.…”
Section: Discussionmentioning
confidence: 99%
“…The study found that 91% of patients reported being satisfied with their surgery, and 92% reported an improvement in their symptoms. In a more recent study by Bouknaitir et al, 2021, patient satisfaction was evaluated after lumbar decompression surgery using a validated questionnaire [16]. The study found that 87% of patients reported being satisfied with their surgery, and 85% would choose to have the same surgery again.…”
Section: Discussionmentioning
confidence: 99%
“…This method was selected to preserve the patient’s unilateral pedicle and lamina and preserve some of the posterior column structures, thus re-establishing postoperative spinal stability and sagittal balance, reducing operative time, bleeding, and improving postoperative healing rates[ 18 ]. A 5-year retrospective study conducted at the New Zealand University Hospital showed no significant differences between reoperation rates and reoperation time between extensive laminectomy, unilateral hemi-laminectomy, and bilateral segmental laminectomy when treating lumbar spinal stenosis[ 19 ]. However, the authors concluded that the spine discipline is moving towards a minimally invasive path, where the same effect of minimizing operative time, the extent of surgery, and incision size was achieved as total laminectomy, with improved patients’ acceptance of surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Propensity scores were calculated using logistic regression analysis with the known preoperative items as explanatory variables [ 18 , 19 , 20 ]. Explanatory variables for logistic regression included age, sex, BMI, smoking, admission type, emergency, hospital type, ADL score, and preoperative comorbidities.…”
Section: Methodsmentioning
confidence: 99%